Review on Type-2 fuzzy in biomedicine - Lathamaheswari, M.; Nagarajan, D.; Udayakumar, A.; Kavikumar, J. (Institute of Medico-Legal Publications, 2018)
Application of physiological and biological ethics to clinical practice is called medical science or Bio-medicine. This branch includes biochemistry, molecular biology, biological engineering neuro science, immunology, pathology and other life science applied to medicine. In this paper, a review has been done for creating a new path and motivation in this field for the new researchers as an application of fuzzy logic in life science areas. Since medical field has uncertainty in nature this topic will be very useful for the future research